Borel Directions and Uniqueness of Meromorphic Functions. (21st August 2013) - Zhang, Keyu; Xu, HongYan; Yi, Hongxun
Abstract : We investigate the relationship between Borel directions and uniqueness of meromorphic functions and obtain some results of meromorphic functions sharing four distinct values IM and one set in an angular domain containing a Borel line. Our result is an improvement of a recent theorem given by Long and Wu (2012).